Combining reformulation, active packaging and non-thermal post-packaging decontamination technologies to increase the microbiological quality and safety of cooked ready-to-eat meat products. (February 2018) - Horita, Claudia N.; Baptista, Rafaela C.; Caturla, Magdevis Y.R.; Lorenzo, Jose Manuel; Barba, Francisco J.; Sant'Ana, Anderson S.
Abstract: Background: Cooked ready-to-eat (RTE) meat products are subjected to contamination of spoilage microorganisms such as lactic acid bacteria and pathogens such as Listeria monocytogenes . These microorganisms contaminate cooked RTE meat products after the cooking step and may further grow during shelf-life potentially leading to spoilage or foodborne diseases, respectively. In the current context of salt, fat and chemical preservatives reduction in meat products formulations, a combined strategy that considers the development of more robust formulations, active packaging and the use of non-thermal post-packaging decontamination strategies seems required to ensure shelf-stable and safe RTE cooked food products. Scope and approach: The main objective of this review was to discuss the aspects related to reformulation, active packaging and the application of non-thermal decontamination technologies at the post-packaging step of cooked RTE meat products, their advantages, limitations and main challenges for their implementation. Key findings and conclusions: In general, post-packaging decontamination technologies aim to reduce or inactivate pathogens and spoilage microorganisms present on the surface of ready-to-eat meat products. Low-temperature plasma, high-pressure processing (HPP), pulsed electric fields, pulsed ultraviolet light and ultrasound are promising alternatives in this segment. However, the choice of the most appropriate approach for post-packaging decontamination of cooked ready-to-eat meat products depends on the type of product and the technological objectives. Meat products formulation and packaging material properties should be considered while defining a post-packaging decontamination approach. Although they are advantageous, non-thermal technologies may present certain limitations such as the increase of oxidative reactions over the shelf-life. Graphical abstract: Highlights: Post-cooking contamination of meat products is a major issue for food industry. Lactic acid bacteria and Listeria monocytogenes are the microorganisms of concern. Intervention could join reformulation, packaging and post-packaging decontamination. Limitations and challenges for the implementation of these methods are discussed.